Correlation between Quality of Life and Gastroesophageal Reflux Disease - Kevin Tandarto; Riki Tenggara; Febie Chriestya; Mario Steffanus (Faculty of Medicine, Universitas Padjadjaran, 2020)
Gastroesophageal reflux disease (GERD) is a disease characterized by the rise of stomach acid into the esophagus which leads to heartburn and regurgitation. The prevalence of adult GERD cases worldwide is 11-38.8%. This study aimed to determine the correlation between GERD and quality of life among patients affected by this disease. This was a cross-sectional study conducted on 92 GERD patients in Atma Jaya Hospital, Jakarta, Indonesia from April 2018 to June 2018. Two questionnaires, GERD-Q and GERD-HRQL were used in this study. A validation of the Indonesian version of the GERD-HRQL questionnaire was performed prior to this study. The Mann Whitney test was used to identify the correlation between GERD and the quality of life in patients with upper gastrointestinal symptoms. This study indicated that the GERD-HRQL questionnaire showed good validity and reliability. Results showed that there was a correlation between GERD and quality of life (p = 0.005) in patients with upper gastrointestinal symptoms. In conclusion, GERD affects the quality of life of patients affected by this disease. Korelasi antara Kualitas Hidup dan Penyakit Refluks GastroesofagusGastroesophageal reflux disease (GERD) atau penyakit refluks gastroesofagus adalah penyakit yang ditandai dengan naiknya asam lambung ke kerongkongan yang menyebabkan sensasi terbakar di dada dan regurgitasi. Prevalensi kasus GERD di seluruh dunia pada orang dewasa adalah 11–38,8%. Penelitian ini bertujuan mengetahui korelasi antara GERD dan kualitas hidup di antara pasien yang terkena penyakit ini. Penelitian dilakukan pada 92 pasien GERD di Rumah Sakit Atma Jaya, Jakarta, Indonesia dari April 2018 hingga Juni 2018. Dua kuesioner, GERD-Q dan GERD-HRQL digunakan dalam penelitian ini. Validasi kuesioner GERD-HRQL versi bahasa Indonesia dilakukan sebelum penelitian ini. Analisis uji Mann Whitney digunakan untuk mengidentifikasi korelasi antara GERD dan kualitas hidup pada pasien dengan gejala gastrointestinal bagian atas. Penelitian ini menunjukkan bahwa kuesioner GERD-HRQL memperlihatkan validitas dan reliabilitas yang baik. Hasil penelitian ini juga menunjukkan erdapat korelasi antara GERD dan kualitas hidup (p=0,005) pada pasien dengan gejala gastrointestinal atas. Simpulan, GERD mempengaruhi kualitas hidup pasien yang terkena penyakit ini.